An introduction to statistics for statistical genetics: models and techniques common in statistical genetics - O'Reilly, Paul (Henry Stewart Talks, 2017)
Hidden Markov models, Imputation and genetic imputation, Principal Component Analysis (PCA), Mixed Models, Shrinkage and regularisation methods